Formation and Development of Andragogy in Ukraine: Historiographic Analysis - Liudmyla Tymchuk; Iryna Kulikovska (Pedagogical Discourse, 2019)
The article fulfills the historiographical analysis of andragogy formation and development in Ukraine, that is the review of the scientific works that in some way affects the andragogy history, that vary in time and place of their publication, as well as each author’s approach originality to the studied educational phenomena. The dissertations on the history of adult education by modern Ukrainian scientists and Russian researchers, scientists of the Soviet period have been analyzed; the researches on the history of educational movement in Ukraine and personality direction have been studied as well. As a result of the historiographical analysis, the researchers’ increased attention to adult education as a social and cultural phenomenon with deep historical traditions and heritage has been discovered. It has been investigated that despite the considerable interest of scientists to this issue, there was no usage of the term «andragogy» in the context of their studies, although almost all authors do not sidestep the theory and practice of human learning in the adulthood. Based on the content analysis of scientific papers, the author makes conclusions about the researchers’ attention to the phenomenon of adult education and its development history. The author notes that existing works do not involve the use of the concept «andragogy», while at the same time almost all researchers, highlighting the history of adult education (either in the context of social movements, or in the light of the Sunday schools, cooperative education development, etc.), do not side-step the issues on the theory and practice of human learning in adulthood. Thus, the author summarizes the novelty of the term «andragogy» for Ukrainian educational vocabulary.